2021
DOI: 10.1038/s41438-021-00638-4
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies QTL for eight fruit traits in cultivated tomato (Solanum lycopersicumL.)

Abstract: Genome-wide association study (GWAS) is effective in identifying favorable alleles for traits of interest with high mapping resolution in crop species. In this study, we conducted GWAS to explore quantitative trait loci (QTL) for eight fruit traits using 162 tomato accessions with diverse genetic backgrounds. The eight traits included fruit weight, fruit width, fruit height, fruit shape index, pericarp thickness, locule number, fruit firmness, and brix. Phenotypic variations of these traits in the tomato colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Out of 18 QTL clusters, 12 QTL clusters exhibited a negative additive effect, indicating the significant contribution of ZS11 toward the investigated traits. We then divided the detected QTL clusters into common and specific clusters ( Kim et al, 2021 ). Based on this, we detected two NPK-common clusters, three K-specific clusters, four N-specific clusters, four PK-specific clusters, three NK-specific clusters, and two NP-specific clusters ( Table 2 and Figure 4 ), suggesting that key loci associated with these traits under multiple environments or treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 18 QTL clusters, 12 QTL clusters exhibited a negative additive effect, indicating the significant contribution of ZS11 toward the investigated traits. We then divided the detected QTL clusters into common and specific clusters ( Kim et al, 2021 ). Based on this, we detected two NPK-common clusters, three K-specific clusters, four N-specific clusters, four PK-specific clusters, three NK-specific clusters, and two NP-specific clusters ( Table 2 and Figure 4 ), suggesting that key loci associated with these traits under multiple environments or treatments.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 20 SNPs significantly associated with fruit width were found. In a previous study, seven SNPs were identified on Ch01 (1), Ch02 (2), Ch03 (1), Ch09 (1), and Ch12 (1) that were linked with tomato fruit width (two) [ 61 ]. Some of the most significantly associated SNPs with flower size were found in genes encoding pentatricopeptide repeat-containing protein At5g14770, probable histone chaperone ASF1A, Ultraviolet-B receptor UVR8, MACPF domain-containing protein At1g14780, G2/mitotic-specific cyclin-1, two-component response regulator ORR21, and adenosine triphosphatase (ARSA1 ATPase) ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tomatoes ( Solanum lycopersicum L.) are a globally important crop cultivated worldwide and are one of the most consumed vegetables ( Kim et al, 2021 ). The silencing of the MutS HOMOLOG1 ( MSH1 ) gene by RNAi affects growth and development.…”
Section: Effect Of Epigenetics On Agronomic Traits In Various Cropsmentioning
confidence: 99%